Annual SPT for Share Investors on BEI after the Ominibus Law Copyration Law Comes into Effect - Dedi Haryadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The enactment of Law number 11 of 2020 on Job Creation since November 2, 2020 is expected to be able to encourage investment and faster economic growth. This Act revised many other laws including the Income Tax Act. The purpose of the study is to determine the impact and implications for the preparation of the annual tax return of stock investors on the IDX. The investors here are retail investors who are individual taxpayers whose tax understanding is not as good as corporate taxpayers. The form of this research is descriptive research. The data collection method is carried out by documentary studies, especially on the Job Creation Act, Government Regulation Number 9 of 2021 and PMK number 18/PMK.03/2021 as well as various kinds of rules related to transactions in the capital market. The results of the study show that the implementation of the Job Creation Act has an effect on the treatment of dividends received by individual investors, so investors who are also personal tax payer must be able to fill out the Annual tax return form properly and correctly according to to the latest provisions so as to avoid potential tax sanctions in the future. The author has described in detail the points of filling out the annual tax return that needs to be done. The author hopes that retail investors are able to take advantage of the dividend exemption given and from the taxation authority side they can revise the rules for granting dividend exemption facilities as non-tax objects with easier regulations.